INTEGRAL STUDY OF THE SILK ROADS ARE COMMERCIAL BUSINESS - Lestari, Bernadetta (Majalah Ekonomi, 2010)
The Silk Roads over land, sea or the steppe, were above all a means of communication and dialogue between civilizations. The exsistence of the routes, whose origins are lost in the mists of time, but whose history can be traced back over more than 2000 years, made an inestimable contribution to the civilization of mankind. At their peak, the Silk Roads took on a significance which was both cultural and commercial. It seemed almost as if the western gate of the city of Chang"An (Xian), capital of China during the Tang dynasty, opened directly into distant countries such as Persia; countries whence arrived not only an immense volume of commercial goods, but olso new ideas. Through these exchanges, countries in the west reaped enermous benefits from the vast sum of knowledge which had enriched the culture of the Chinese capital. These routes extended even beyond the practical terminal points in the MiddleEast and China, westwards as far as Rome or Venice and eastwards as far as Nara. (Draff. Unesco)